Mechanistic Studies in Photocatalysis. Issue 12 (15th January 2019) - Buzzetti, Luca; Crisenza, Giacomo E. M.; Melchiorre, Paolo
Abstract: The fast‐moving fields of photoredox and photocatalysis have recently provided fresh opportunities to expand the potential of synthetic organic chemistry. Advances in light‐mediated processes have mainly been guided so far by empirical findings and the quest for reaction invention. The general perception, however, is that photocatalysis is entering a more mature phase where the combination of experimental and mechanistic studies will play a dominant role in sustaining further innovation. This Review outlines the key mechanistic studies to consider when developing a photochemical process, and the best techniques available for acquiring relevant information. The discussion will use selected case studies to highlight how mechanistic investigations can be instrumental in guiding the invention and development of synthetically useful photocatalytic transformations. Abstract : Lighting the (reaction) path : Photoredox and photocatalysis have recently provided fresh opportunities to expand the potential of organic synthesis. So far, innovation has mainly been driven by the quest for novel reactivities, often at the expense of a thorough mechanistic understanding. But these fields are now entering a more mature phase where the combination of experimental and mechanistic studies will play a dominant role in sustaining further innovation.